234k views
0 votes
Simplify the radical expression attached below.

Simplify the radical expression attached below.-example-1
User Alex Riina
by
5.5k points

2 Answers

4 votes
It’s gonna be radical 10x/ 4x.
User Vikas Gupta
by
5.2k points
3 votes
Answer:
(√(10x))/(4x)

===========================================================

Work Shown:

The idea is to multiply top and bottom by sqrt(8x) to make the denominator rational (ie get rid of the square root)


(√(5))/(√(8x)) = (√(5)*√(8x))/(√(8x)*√(8x))


(√(5))/(√(8x)) = (√(5*8x))/(√(8x*8x))


(√(5))/(√(8x)) = (√(40x))/(√((8x)^2))


(√(5))/(√(8x)) = (√(4*10x))/(8x)


(√(5))/(√(8x)) = (√(4)*√(10x))/(8x)


(√(5))/(√(8x)) = (2*√(10x))/(8x)


(√(5))/(√(8x)) = (√(10x))/(4x)

where x > 0 for each step shown above

note: refresh the page if the math symbols do not show up

User Kmfk
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.